Optical fiber sensor review - Wang, Guoqing (2014)
This review paper provides a basic idea of the optical fiber developed from its very first beginning being used to sensing purpose till the advance application to various type of sensor in different field. The studying of the fiber structure and its working principle helped us to understand and enable us to create new type of fiber sensor in many areas. The optical fiber pH sensor is the main topic in this article. Using sol-gel technologies and layer-by-layer self-assembly method with special detection materials, a fiber pH meter could be very sensitive to a slight change of the tested solution. Broad testing ranges make the sensor more suitable for extreme environmental conditions. Numbers of instruments were used to determine the performance of the pH sensor.